Treatment of idiopathic hypersomnia with modafinil in an individual at clinical high risk for psychosis: A case report - Yutaro Sato; Atsushi Sakuma; Hiroaki Tomita (PCN Reports)
Abstract Background Recent studies have shown that sleep disturbances are frequent at different stages of psychosis, including clinical high risk for psychosis (CHR‐P). However, the comorbidity of hypersomnia with CHR‐P and its treatment have rarely been reported or discussed. Case Presentation A 16‐year‐old female diagnosed with major depressive disorder and CHR‐P experienced worsening excessive daytime sleepiness (EDS), including falling sleep in class. Polysomnography and multiple sleep latency tests confirmed the diagnosis of idiopathic hypersomnia (IH), and treatment with modafinil (100 mg/day) was initiated. EDS improved after increasing the modafinil dose to 200 mg/day. No side effects or exacerbations of psychotic symptoms were observed. EDS recurred after she entered university and was treated with 300 mg/day of modafinil without side effects or transition to psychosis. Conclusion This case demonstrates modafinil's efficacy and safety in treating IH in individuals with CHR‐P. However, whether modafinil use increases the risk of transition to psychosis remains unclear. Further research is required on modafinil as a treatment for hypersomnia in individuals with CHR‐P.